2009
DOI: 10.1186/1471-2164-10-613
|View full text |Cite
|
Sign up to set email alerts
|

Increased epithelial stem cell traits in advanced endometrial endometrioid carcinoma

Abstract: BackgroundIt has been recognized cancer cells acquire characters reminiscent of those of normal stem cells, and the degree of stem cell gene expression correlates with patient prognosis. Lgr5(+) or CD133(+) epithelial stem cells (EpiSCs) have recently been identified and these cells are susceptible to neoplastic transformation. It is unclear, however, whether genes enriched in EpiSCs also contribute in tumor malignancy. Endometrial endometrioid carcinoma (EEC) is a dominant type of the endometrial cancers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Also at 12 h of gefitinib treatment, APBA2 and RSP2, previously found to be highly expressed in endometrial carcinomas [36] and prostate cancer [37], respectively, were inhibited. However, by 24 h treatment (Additional File 10, Figure S9), Hec50co cells demonstrated a transcriptional response that may be compensatory to the anti-proliferative effects of gefitinib in that some genes associated with malignant transformation and tumor progression were induced.…”
Section: Discussionmentioning
confidence: 94%
“…Also at 12 h of gefitinib treatment, APBA2 and RSP2, previously found to be highly expressed in endometrial carcinomas [36] and prostate cancer [37], respectively, were inhibited. However, by 24 h treatment (Additional File 10, Figure S9), Hec50co cells demonstrated a transcriptional response that may be compensatory to the anti-proliferative effects of gefitinib in that some genes associated with malignant transformation and tumor progression were induced.…”
Section: Discussionmentioning
confidence: 94%
“…It is clear that cancer cells possess traits that are reminiscent of those ascribed to normal stem cells and that the degree of stem cell gene expression correlates with patient prognosis. Histologically poorly differentiated tumors or late-stage tumors show preferential overexpression of genes that are normally enriched in ES cells (ESCs) or in somatic stem cells, which may partly explain why these tumors are more malignant [ 22 , 23 ]. We hypothesized that the distinct clinical survival trends of different PEBTs might be reflected by their gene expression traits.…”
Section: Resultsmentioning
confidence: 99%
“…The stem cell genes expression was correlated with tumor prognosis in endometrial cancer. Advanced endometrioid tumors had a positive association with epithelial stem cells (EpiSCs) genes [62] Some of the stemness genes included in this signature were ADAM17 (A Disintegrin and A Metalloproteinase 17), CAP1 (adenylate cyclase-associated protein 1), PDCD10 (CCM3), PSEN1 (presenilin 1) and SENP2 (SUMO-specific protease 2) [62].…”
Section: Endometrial Cancer Stem Cellsmentioning
confidence: 99%
“…Chang et al studied a signature of EpiSC genes and found a total of 26 genes overexpressed in advanced endometrioid tumors [62]. The CD133+ cells were isolated from endometrial tumors by flow cytometry, representing an average of 18.1 % (1.3 to 61.6 %) [79] The staining of CD133/1 antibody was diffuse and the epithelial tumor cells expressed Tn-MUC1 glycoform.…”
Section: Endometrial Cancer Stem Cellsmentioning
confidence: 99%